Estratégias multireferenciais na gestão do desporto adaptado ao idoso - Nascimento, Amanda Mayara (2012)
This qualitative study aimed at investigating the multireferencials strategies for adherence and maintenance in regular physical activity by elderly. The study consisted of exploratory research, developed based on participant observation technique, and had as categories for analysis: the motivation for adherence to the activities, the spontaneous constancy and maintenance, the emotional states involved and the adaptations made. The population of the study was consisted by 30 elderly of both sexes, regularly engaged in the program "Physical activity and health for the elderly" offered by UFLA, Minas Gerais State, Brazil. Data were descriptively analyzed and indicate that multireferecials strategies received wide acceptance due to be suitable for this group, by encouraging adherence and maintenance in activities and for instigating positive emotional involvement.